2014
DOI: 10.3892/mmr.2014.2696
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interaction network and mechanism analysis in ischemic stroke

Abstract: Ischemic stroke is a leading cause of mortality and permanent disability, with enormous financial repercussions on health systems worldwide. Ischemic brain injury results from a complex sequence of pathophysiological events that evolve over time. In order to examine the molecular mechanisms underlying middle cerebral artery occlusion (MCAO)-induced ischemic stroke, the GSE35338 affymetrix microarray data was obtained from the Gene Expression Omnibus database and the differentially expressed genes (DEGs) betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…Many important biological processes were revealed in our study, such as cell death, programmed cell death, MAPK signaling pathway, which are consistent with the findings of previous studies 14 . There were 5 phosphate-related processes in the unique biological processes of module 8, accounting for 17.24%.…”
Section: Discussionsupporting
confidence: 93%
“…Many important biological processes were revealed in our study, such as cell death, programmed cell death, MAPK signaling pathway, which are consistent with the findings of previous studies 14 . There were 5 phosphate-related processes in the unique biological processes of module 8, accounting for 17.24%.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous murine ischemic stroke studies have noted that CXCL10 is significantly upregulated within the ischemic region after both transient and permanent middle cerebral artery occlusion . In one of these studies, inhibition of IFN‐ γ signaling prior to middle cerebral artery occlusion blocked induction of CXCL10 and reduced infarct volume, T‐cell infiltration, and neurodegeneration .…”
Section: Discussionmentioning
confidence: 99%
“…Hematopoietic cell lineage and Cytokine-cytokine receptor interaction were also found in middle cerebral artery occlusion induced ischemic stroke mice (Quan et al 2015). Furthermore, a recent study showed affected Ribosome, Toll-like receptor signaling pathway, MAPK signaling pathway, and Chemokine signaling pathway in the ischemic rodent brain (Liang et al 2015).…”
Section: Discussionmentioning
confidence: 96%
“…And it's produced by many different cells including monocytes, macrophages, fibroblasts, endothelial cells, keratinocytes, mast cells, T-lymphocytes, and also by microglia and astrocytes (Ferrarese et al 1999). An increasing number of experimental observations showed that IL6 plays a central role in the pathogenesis of several ischemic cardiovascular disorders, including ischemic stroke (Quan et al 2015). A recent report suggested that IL6…”
Section: Discussionmentioning
confidence: 99%